Translation of the Pasieka’s Parathyroid Assessment of Symptoms Questionnaire (PAS-Q) for Use in the Greek Population - Tzikos, Georgios; Manani, Christina; Adamidou, Fotini; Menni, Alexandra; Moysidis, Moysis; Tsalkatidou, Despoina; Chorti, Angeliki; Kotsa, Kalliopi; Toulis, Konstantinos; Anagnostis, Panagiotis; Michalopoulos, Antonios; Papavramidis, Theodosios (Frontiers in Endocrinology, 2022)
Introduction: In Europe, primary hyperparathyroidism is mainly considered an asymptomatic disorder, although there is evidence that patients’ health-related quality of life is impaired. This aspect is mostly evaluated using Pasieka’s Questionnaire: a disease-specific diagnostic tool. The purpose of this study was to translate the Pasieka’s Questionnaire into the Greek language and adapt it to the Greek population. Materials and Methods: Pasieka’s Questionnaire consists of 13 questions. Two bilingual, native Greek experts were selected for step one, each of whom offered a blinded Greek version of the questionnaire. In the second step, these two versions were merged into one which was retranslated back into the English language (step three) by two bilingual translators (English native speakers). In the fourth step, a committee was formed to draft the pre-final version of the questionnaire which was then submitted to the co-authors for final approval. Finally, after the approval of the final version, 50 patients with primary hyperparathyroidism were recruited for the pilot study of the questionnaire. Results: All 13 questions of the Pasieka’s Questionnaire were translated without any major discrepancy. A high level of internal consistency was achieved (Cronbach’s alpha was 0.904) and agreement between test-retest was excellent for every question. Conclusion: The Greek version of Pasieka’s Questionnaire was validated and can be applied to evaluate the health-related quality of life of patients with primary hyperparathyroidism in Greek-speaking populations.